Retinal nerve fiber layer assessment in healthy children using scanning laser polarimetry with variable corneal compensation - Filouš, Aleš; Hložánek, Martin; Ošmera, Jakub; Hladíková, Marie (Journal of AAPOS, 2008)
To assess the normative data of the retinal nerve fiber layer (RNFL) thickness in healthy children using the scanning laser polarimeter with variable corneal compensation (GDxVCC). METHODS: Of the 186 enrolled white school-aged children, 120 subjects of the mean 12.85 +/- 3.0 years (age +/- SD) fulfilled inclusion criteria. After complete ophthalmic examination, including GDxVCC, 240 normal eyes were analyzed. Evaluation of RNFL thickness in GDxVCC temporal-superior-nasal-inferior-temporal (TSNIT) parameters was performed, and probability of normality was calculated. The influence of sex and age was investigated. RESULTS: The mean +/- SD values in TSNIT Average, Superior Average, Inferior Average, and TSNIT SD were 58.98 +/- 6.92 microm, 72.99 +/- 8.97 microm, 71.18 +/- 10.92 microm, and 26.30 +/- 4.92 microm. The values of 5% probability of normality in the same order were 47.6 microm, 58.2 microm, 53.2 microm, and 18.2 microm. The mean values of Inferior Average and TSNIT SD were greater in left eyes by 1.84 +/- 6.6 microm (p = 0.003) and by 3.04 +/- 3.8 microm (p < 0.00005), respectively. No correlation to sex and age was found. CONCLUSIONS: RNFL thickness assessed using GDxVCC was greater in children compared with previous published data in healthy adults. The values of Inferior Average and TSNIT SD were significantly greater in left eyes.
Keywords: diagnostické techniky oftalmologické; dítě; Retina; rohovka; Adolescent; Cornea; dvojitý lom; lidé; Probability; referenční hodnoty; pravděpodobnost; Diagnostic Techniques, Ophthalmological; Lasers; počítačové zpracování obrazu; Reference Values; Birefringence; lasery; Child; retina; Nerve Fibers; nervová vlákna; mladiství; Image Processing, Computer-Assisted; Humans